(untitled) (Movimenta (ISSN 1984-4298), 2021)
Objective: to investigate the state of the art in the literature about the impacts of low weekly frequency of physical activity on the health of its supporters. Methods: In this integrative review, the Pubmed and Scielo databases were consulted, using the following descriptors: "Physical exercise", "Weekend Warrior", "health promotion", without restriction as to the year of publication. Results: Eight studies were carried out on different continents and published between 2000 and 2019, which showed associations between individuals adept at practicing low-frequency weekly physical activity and reducing mortality, compared with physically inactive individuals. In addition, benefits in mental health, decrease in body composition, a better appreciation of health status, and reduction of smoking. Consistent evidence was identified in the findings, in addition to recommendations for future investigations. Conclusion: Although the regular practice of physical activity with a minimum frequency of three times a week is usually recommended, one should consider its applicability in the routine of daily life. Research on the less frequent practice of a physical activity is necessary, given its positive impact on different health outcomes.